2018
DOI: 10.1002/jor.24029
|View full text |Cite
|
Sign up to set email alerts
|

Paravertebral injection of botulinum toxin‐A reduces lumbar vertebral bone quality

Abstract: Aging has been associated with decreases in muscle strength and bone quality. In older patients, paravertebral muscle atrophy tends to coincide with vertebral osteoporosis. The purpose of this study was to investigate the effects of a paravertebral injection of botulinum toxin-A (BTX) on paravertebral muscle atrophy and lumbar vertebral bone quality. Forty 16-week-old female SD rats were randomly divided into four groups: (1) a control group (CNT); (2) a resection of erector spinae muscles group (RESM); (3) a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several studies have shown a strong association between fatty infiltration of the multifidus muscle and lumbar BMD [ 25 , 26 ]. Wang et al [ 13 ] conducted an experimental study in rats and found that bone loss occurred in rats with paraspinal muscular atrophy compared with that in controls. They concluded that preserving the muscle tissue around the lumbar spine during clinical surgery was important to prevent the loss of lumbar spine bone quality and mass [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown a strong association between fatty infiltration of the multifidus muscle and lumbar BMD [ 25 , 26 ]. Wang et al [ 13 ] conducted an experimental study in rats and found that bone loss occurred in rats with paraspinal muscular atrophy compared with that in controls. They concluded that preserving the muscle tissue around the lumbar spine during clinical surgery was important to prevent the loss of lumbar spine bone quality and mass [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 13 ] conducted an experimental study in rats and found that bone loss occurred in rats with paraspinal muscular atrophy compared with that in controls. They concluded that preserving the muscle tissue around the lumbar spine during clinical surgery was important to prevent the loss of lumbar spine bone quality and mass [ 13 ]. Jin et al [ 27 ] found that skeletal muscle satellite cells that adhere to muscle fibers play a crucial role in the repair of osteoporotic fractures, maintaining their differentiation into osteoblasts and restricting osteoclastogenesis through the β-catenin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, BoNT/Ainduced masticatory muscle atrophy can promote mandibular loss [23]. Wang et al also discovered that injecting BoNT/A into paraspinal muscles could lead not only to muscle atrophy and dysfunction, but also to local bone loss and quality loss of the lumbar spine [24].…”
Section: Potential Mechanisms For Diseases Caused By Bont/amentioning
confidence: 99%